The Psychological Impact of the COVID-19 Pandemic on Teenagers in China - Zhang, Caiyun; Ye, Maolin; Fu, Yunwei; Yang, Minyi; Luo, Fen; Yuan, Jinhua; Tao, Qian (Journal of adolescent health, 2020)
The 2019 COVID-19 pandemic poses a challenge to adolescent psychological health. The aim of this study was to survey junior high and high school students in China to better understand the psychological consequences, such as anxiety, depression, and stress, of the COVID-19 pandemic. A cross-sectional online survey using structural questionnaires was conducted from April 7, 2020, to April 24, 2020. Demographic information and general information related to the pandemic were collected. Psychological consequences were assessed by the Impact of Event Scale-Revised and the Depression, Anxiety and Stress Scale. Influencing factors were assessed by the Brief Resilience Scale and Coping Style Questionnaire. Our sample comprised 493 junior high school students (male = 239, mean age = 13.93 years) and 532 high school students (male = 289, mean age = 17.08 years). Resilience and positive coping were protective factors for the occurrence of depressive, anxiety, and stress symptoms in junior high and high school students (p < .05). Positive coping was a protective factor for trauma-related distress in junior high school students (p < .05). Negative coping is a risk factor for depression, anxiety, stress symptoms, and trauma-related distress in junior high and high school students (p < .05). During the COVID-19 pandemic in China, more than one fifth of junior high and high school students' mental health was affected. Our findings suggested that resilience and positive coping lead to better psychological and mental health status among students. In contrast, negative coping is a risk factor for mental health.